Modelled estimates of fine sediment and particulate nutrients delivered from the Great Barrier Reef catchments. (April 2021) - McCloskey, G.L.; Baheerathan, R.; Dougall, C.; Ellis, R.; Bennett, F.R.; Waters, D.; Darr, S.; Fentie, B.; Hateley, L.R.; Askildsen, M.
Abstract: The eWater Source modelling framework has been modified to support the Great Barrier Reef (GBR) Dynamic SedNet catchment modelling concept, which is used to simulate fine sediment and particulate nutrient generation, loss, and transport processes across GBR catchments. Catchment scale monitored data sets are used to calibrate and evaluate models. Model performance is assessed qualitatively and quantitatively. Modelling predicts that approximately half of generated sediment is delivered to the GBR lagoon; the remainder is deposited on floodplains, trapped in reservoirs or lost through other minor processes (e.g. irrigation extractions). Gullies are the major source of sediment, with comparable contributions from hillslopes and streambanks. Hillslope sources are considered the major source of particulate nutrients across the GBR catchments. We demonstrate that using locally developed, customised models coupled with a complementary monitoring program can produce credible modelled estimates of pollutant loads and provide a platform for testing catchment scale assumptions and scenarios. Highlights: The Great Barrier Reef (GBR) Dynamic SedNet model estimates fine sediment and particulate nutrients exported to the GBR. The eWater Source modelling framework was coupled to agricultural systems models. Constituent sources and sinks are modelled at a daily time-step, at the subcatchment-land-use scale. A range of catchment scale monitored and historical modelled data sets are used to calibrate and evaluate modelled loads. Models predict 8, 490 kt/yr fine sediment, 21, 477 t/yr and 9, 045 t/yr particulate nitrogen and phosphorus is exported.